Analisis keselamatan dan kesehatan kerja (K3) pada pekerja di lingkungan Minas Gas Turbine (MGT) PT. Chevron Pacific Indonesia (CPI), Minas - Ali Amran; Bintal Amin; Sofia Anita (Pelantar Press, 2021)
Human resources play an important role for the success of an organization or company, because humans are living assets that need special attention by the company. The fact that humans as a major asset in an organization or company must get serious attention and be managed as well as possible. In managing human resources, management is needed to be able to manage resources systematically, planned and efficiently. Of the many companies that move at high levels of potential hazards, one of them is the Oil and Gas Mining sector and in this sector work accidents often occur. In general, accidents are always interpreted as